Sears owner Caylor left in lurch by closing - Wasserstrom, David (Raton, NM Raton Range, 1993)
This article is about the Sears catalog and J. C. Penny store closing
Newspaper article + photograph of Ivan Caylor
Master list item #: 65
File location is in the Raton file Cabinet
Keywords: Caylor, Ivan; Raton Sears Catalog Store; J. C. Penny; Business closings; Local Business; Retail Stores; Owner History; Raton, New Mexico